Mobilization of Violence under the Guise of Religion Against the Ahmadiyya Minority in Indonesia: A Lesson from the Past - Herdi Sahrasad; Dedy Tabrani; Iskandar Zulkarnain; Ti Aisyah; Mai Dar (ESENSIA: Jurnal Ilmu-Ilmu Ushuluddin, 2026)
In the past (2004-2014), the Ahmadiyah minority in Indonesia all too often faced attacks and violence from Muslim groups claiming to act in the name of religion. During this period, there was a mobilization of violence against the Ahmadiyah community, referring to efforts to rally Muslims to carry out violent actions. This term encompasses various contexts, ranging from mass mobilization in social conflicts to more organized movements aimed at spreading violence. These Muslim groups committed brutal acts of intolerance and violated the human rights of the Ahmadiyah community, who were persecuted for their choice of belief based on personal conscience. The government of President Susilo Bambang Yudhoyono (2004–2014) failed to protect the Ahmadiyah congregation as a minority group in Indonesia and to uphold the constitutional guarantees enshrined in the 1945 Constitution and the state foundation of Pancasila, which guarantee freedom of religion and worship for the community. all citizens. Violence against the Ahmadiyah minority reflects a deep-rooted pattern of violence in Indonesia that has persisted and expanded in society since the collapse of Suharto’s New Order authoritarian regime in 1998. Learning from the mistakes of the past, it is clear that religious pluralism and diversity remain unresolved and serious challenges in Indonesia, a nation founded on the noble ideology of Pancasila, which promotes tolerance.